Beginning Google Maps Applications with PHP and Ajax From Novice to Professional - Sambells, Jeffrey; Purvis, Michael; Turner, Cameron (Apress : Imprint: Apress, 2006)
Until recently, building interactive web-based mapping applications has been a cumbersome affair. This changed when Google released its powerful Maps API. Beginning Google Maps Applications with PHP and Ajax was written to help you take advantage of this technology in your own endeavorswhether you're an enthusiast playing for fun or a professional building for profit. This book covers version 2 of the API, including Google's new Geocoding service. Authors Jeffrey Sambells, Cameron Turner, and Michael Purvis get rolling with examples that require hardly any code at all, but you'll quickly become acquainted with many facets of the Maps API. They demonstrate powerful methods for simultaneously plotting large data sets, creating your own map overlays, and harvesting and geocoding sets of addresses. You'll see how to set up alternative tile sets and where to access imagery to use for them. The authors even show you how to build your own geocoder from scratch, for those high-volume batch jobs. As well as providing hands-on examples of real mapping projects, this book supplies a complete reference for the Maps API, along with the relevant aspects of JavaScript, CSS, PHP, and SQL. Visit the authors' website for additional tips and advice.